Transcriptome and protein interaction profiling in cancer cells with mutations in histone H3.3 - Lim, Jinyeong; Park, Joo Hyun; Baude, Annika; Fellenberg, Joerg; Zustin, Jozef; Haller, Florian; Kruecken, Irene; Kang, Hyun Guy; Park, Yoon Jung; Plass, Christoph; Lindroth, Anders M. (Scientific Data, 2018)
Mutations of histone variant H3.3 are highly recurrent in childhood glioblastoma and in young adults with Giant Cell Tumor of the Bone (GCTB). The heterozygotic representation of the mutations in the tumors, and with potential histone H3 and H3.3 redundancy, suggest that the mutations are gain-of-function by nature. To address common H3.3 point mutations, we have generated data from GCTB patient samples with H3.3 G34W substitutions and engineered human GFP-tagged H3.3-mutated isogenic cell lines for high throughput data comparisons. First, a total of thirty-six patient samples and cell lines were used to acquire gene expression transcriptome data using microarray and RNA-sequencing. The expression data were validated with the orthogonal nCounter assay. Second, to uncover the H3.3-GFP interaction proteomes from the isogenic cell lines, immunoprecipitation of unmutated wild type, K27M, G34R, and G34W substitutions were performed. The RNA-sequencing data and the H3.3 interaction proteome enable potentially important functional insight into the tumorigenic process and should spur further detailed analysis.
EVALuna2:207061